Similar Frequencies of Pseudomonas aeruginosa Isolates Producing KPC and VIM Carbapenemases in Diverse Genetic Clones at Tertiary-Care Hospitals in Medellin, Colombia (2014)
ABSTRACT : Carbapenem-resistant Pseudomonas aeruginosa has become a serious health threat worldwide due to the limited options available for its treatment. Understanding its epidemiology contributes to the control of antibiotic resistance. The aim of this study was to describe the clinical and molecular characteristics of infections caused by carbapenem-resistant P. aeruginosa isolates in five tertiary-care hospitals in Medellín, Colombia. A cross-sectional study was conducted in five tertiary-care hospitals from June 2012 to March 2014. All hospitalized patients infected by carbapenem-resistant P. aeruginosa were included. Clinical information was obtained from medical records. Molecular analyses included PCR for detection of blaVIM, blaIMP, blaNDM, blaOXA-48, and blaKPC genes plus pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) for molecular typing. A total of 235 patients were enrolled: 91.1% of them were adults (n 214), 88.1% (n 207) had prior antibiotic use, and 14.9% (n 35) had urinary tract infections. The blaVIM-2 and blaKPC-2 genes were detected in 13.6% (n 32) and 11.5% (n 27), respectively, of all isolates. Two isolates harbored both genes simultaneously. For KPC-producing isolates, PFGE revealed closely related strains within each hospital, and sequence types (STs) ST362 and ST235 and two new STs were found by MLST. With PFGE, VIM-producing isolates appeared highly diverse, and MLST revealed ST111 in four hospitals and five new STs. These results show that KPC-producing P. aeruginosa is currently disseminating rapidly and occurring at a frequency similar to that of VIM-producing P. aeruginosa isolates (approximately 1:1 ratio) in Medellín, Colombia. Diverse genetic backgrounds among resistant strains suggest an excessive antibiotic pressure resulting in the selection of resistant strains.